Simulation of Long-Term Changes of the Equilibrium Line Altitude in the Central Chilean Andes Mountains Derived From Atmospheric Variables During the 1958-2018 Period - Barria, Ignacio; Carrasco Cerda, Jorge Fernando; Casassa, Gino; Barria, Pilar (My University, 2019)
Interannual variability and trends of the Equilibrium Line Altitude (ELA) in the Andes mountains can be modeled using an empirical relationship between the annual average of the 0 degrees C isotherm altitude (ZIA) and the annual precipitation accumulated in mountain areas. Based on updated daily radiosonde profiles, and multiple sources of precipitation data recorded in the central Chile (30-38 degrees S) mountain region, the variability and trend analyses of the ELA time series previously available until 2006 were extended to 2018, to investigate the occurrence and causes of ELA changes in both: the long term and during the last decade. According to the analyses, the annual ELA has presented an overall increase in the central Chilean Andes of about similar to 114 +/- 21 m (p < 0.1) during the 1958-2018 period, much larger than the similar to 54 m reported in previous studies for the 1958-2006 period. Furthermore, the changes in the annual ELA has enhanced during the last decades, showing significant increases of similar to 405 +/- 55 m (p < 0.05) between 2000 and 2018 in the same region. Those trends are associated to changes in ZIA and predominantly to decreases in annual precipitation. The ZIA analyses indicate increments of about 127 +/- 10 m (p < 0.05) and 82 +/- 15 m (non-statistically significant) for the 1958-2018 and 2000-2018 period, respectively. Moreover, an unprecedent and uninterrupted period of consecutive dry years with deficits of about 30% in annual rainfall, the so-called Megadrought, has affected central Chile between 2010 and 2018 further affecting the snow accumulations in mountain areas and leading to increases in ELA. The results also indicate important multidecadal variability, which according to the literature can be associated to changes in the Pacific Decadal Oscillation (PDO). Concurrently with the PDO shift that took place in 1976/77, the annual ELA in the central Chilean Andes showed a decrease of -68 +/- 12 m (non-statistically significant) between 1958 and 1976, and a significant increase of similar to 265 +/- 32 m (p < 0.05) between 1978 and 2018.
Keywords: zero isotherm altitude; equilibrium line altitude; central chile; andes mountains; upper-air temperature; mountain precipitation